Waiting Time Analysis of Passenger Vessels in Jamrud North Terminal Surabaya - Sepfani, Ade Putri; Akhmad, Ekka Pujo Ariesanto; Saputra, Toto Dwijaya (Universitas Hang Tuah, 2025)
This research aims to analyze the waiting time for passenger ships at the North Jamrud Terminal, Surabaya. This research method used a qualitative method with a descriptive approach. The data sources used are primary data and secondary data with data collection techniques in the form of interviews with 4 office staff and 1 SPJM manager, direct observation and documentation. The results of this research show that there are still waiting times that do not meet port performance standards at the North Jamrud Terminal, Surabaya. Waiting time for passenger ships at the Jamrud Utara terminal in Surabaya is influenced by several factors such as bad weather such as heavy rain and storms, making it difficult for ships to dock at the pier and extending the ship's time aloft. Inconsistency in the ship's arrival schedule, whether the ship arrives earlier than scheduled or late. As well as the effectiveness of guide services, guide services that are not optimal in busy water situations can worsen waiting times. The results of the analysis for the period October to December 2023, the waiting time at the Jamrud Utara terminal in Surabaya reached 2.53 hours, so it does not comply with port performance standards. Meanwhile, the ship's approach time at the North Jamrud Terminal, Surabaya, shows that the port service performance is good, because it is below the average approach time standard at the North Jamrud Terminal, Surabaya.